Ce and Y doped ZrO2 biological ceramic material as well as preparation method and application thereof

By introducing Ce and Y doping elements into ZrO2 ceramic powder, nano-scale CexYxZr ceramic powder is prepared by sol-gel method, the problem of poor single-climb phase stability of pure ZrO2 ceramic powder at room temperature is solved, and the ceramic material is realized Improved mechanical properties and potential application value of dental restoration materials.

CN119191837APending Publication Date: 2024-12-27RES & DEV INST OF NORTHWESTERN POLYTECHNICAL UNIV IN SHENZHEN +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411297948.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Pure ZrO2 ceramic powder mainly has a single-clind phase structure at room temperature, resulting in poor mechanical properties, and may undergo phase transition during sintering and cooling, causing the ceramic product to crack, and cannot be used as a stable dental restoration material.

Method used

The sol-gel method is used to introduce Ce and Y doped elements into ZrO2 ceramic powder. By controlling the grain size is less than 17nm, the tetragonal phase structure is stabilized, and its stability and fracture toughness at room temperature are improved. Acrylamide and N are used. N-methylenebisacrylamide is used as a polymerizer and ammonium persulfate is used as an inducer to form a nano-scale CexYxZr ceramic powder.

Benefits of technology

The existence of a stable tetragonal phase structure at room temperature is achieved, the mechanical properties and fracture toughness of ceramic materials are improved, the service life is extended, the sintering temperature and time is reduced, and the application prospects of dental restoration materials are expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191837A_ABST
    Figure CN119191837A_ABST
Patent Text Reader

Abstract

The invention relates to a Ce and Y doped ZrO2 biological ceramic material and a preparation method and application thereof, and relates to the field of multifunctional oxide powder materials and preparation thereof.ZrO2 serves as a matrix, a sol-gel method is adopted, two doping elements are introduced into ZrO2, and finally the ZrO2 doped biological ceramic powder material with the average powder grain size smaller than 17 nm is obtained. The minimum grain size is about 14 nm, the ZrO2 ceramic powder material subjected to doping treatment can be further prepared into a nanoscale biological ceramic block material through a sintering process, and the ZrO2 ceramic powder material has potential application value in the field of dental restoration materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of multi-element doped oxide powder materials and their preparation technology, and relates to a Ce and Y co-doped ZrO2 bioceramic material and its preparation method and application Background Art

[0002] ZrO2 ceramic powder has three structures, namely monoclinic phase, tetragonal phase and cubic phase, which can be transformed into each other under certain temperature conditions. Pure ZrO2 ceramic powder (undoped) is a monoclinic phase structure at room temperature, but at high temperature, it has two structures, tetragonal phase and cubic phase, which have poor stability at room temperature. Studies have shown that the more tetragonal phase structure ZrO2 ceramic products contain, the better their comprehensive mechanical properties are. It is an important candidate material in the field of dental restoration and has potential application value.

[0003] Although ZrO2 ceramics have many advantages, they still face some limitations in practical applications and still have shortcomings that need to be improved. For example, at room temperature, pure ZrO2 ceramic powder mainly exists in a monoclinic phase structure at room temperature, and the mechanical properties of ZrO2 ceramics prepared using this ceramic powder are extremely poor. Pure ZrO2 ceramic materials will undergo a phase transition during the sintering cooling process, from a tetragonal phase to a monoclinic phase, accompanied by volume expansion, which causes the ceramic products to crack and are not capable of being used as dental restoration materials. Therefore, exploring and developing a preparation method that stabilizes the tetragonal phase structure of ZrO2 at room temperature has become the focus of researchers' work.

[0004] To solve these problems, based on the principle of phase transition caused by ZrO2, many researchers have begun to focus on the composition design and preparation process development of ZrO2 ceramic powder in recent years. By introducing doping elements, lattice distortion is introduced and grain boundary density is increased in pure ZrO2 ceramic powder. Doping causes lattice distortion inside ZrO2 ceramics, which can inhibit the transformation of the tetragonal phase to the monoclinic phase of ZrO2 at room temperature, thereby achieving the purpose of stabilizing the tetragonal phase at room temperature, thereby improving its mechanical properties as a dental restoration material and extending its service life. At the same time, the introduction of lattice distortion and grain boundary density can effectively prevent crack propagation, improve the fracture toughness of zirconia ceramic materials, and expand its application prospects as a ZrO2 matrix material in the field of dental restoration materials.

[0005] Nanomaterials refer to substances with at least one dimension less than about 100nm. When designing multi-element doped ZrO2 ceramic powder, the grain size is reduced to the nanoscale, which is beneficial to the preparation of nano-level ZrO2 ceramics during sintering. When the ceramic grain size reaches the nanoscale, its grain boundary density increases, which can effectively hinder its crack propagation; at the same time, nano ceramic powder has a high sintering activity, which can reduce the ceramic sintering temperature, shorten the sintering time, increase the density of the ceramic, and further improve its mechanical properties.

[0006] For example, Zhang Jianxing et al. (Jianxing Z, Zongyu F, Jianhui S, et al. Crystal defects and phase transitions of nanocrystalline yttria-stabilised zirconiainduced by high-energy ball milling. Ceramics International, 2021, 47 (12): 6432-16440.) Y-doped ZrO2 powder prepared by high-energy ball milling has a minimum particle size of about 130 nm. However, the high-energy ball milling preparation cycle is long, the prepared powder particle size is relatively large and unevenly distributed, and the mixing of multiple elements is insufficient. Therefore, the present invention aims to provide a method for preparing a doped ZrO2 ceramic powder with a finer grain size using a sol-gel method. Summary of the invention

[0007] Technical issues to be solved

[0008] In order to avoid the shortcomings of the prior art, the present invention proposes a Ce and Y doped ZrO2 bioceramic material and its preparation method and application, and provides a method for preparing nano-scale doped ZrO2 ceramic powder using a sol-gel method, which greatly optimizes the properties of the doped ZrO2 ceramic such as tetragonal phase structure stability and fracture toughness at room temperature.

[0009] Technical Solution

[0010] Preparation of nano-scale Ce by sol-gel method x Y x The method of Zr ceramic powder material is characterized by the following steps:

[0011] Step 1: Dissolve the zirconium oxide raw material and dopant in an aqueous solution, add while stirring at room temperature until they are completely dissolved to obtain a transparent solution A;

[0012] The zirconium oxide raw material Zr +4The ratio of the molar mass to the total molar amount of metal cations of the dopant is 1:0.01-0.1;

[0013] Step 2: Add the polymerizing agent and the inducing agent to solution A, stirring at room temperature until they are completely dissolved to obtain a light yellow transparent solution B;

[0014] Step 3: Solution B is heated in a water bath to near the gel point, and a milky white gel begins to form until it is completely gelled;

[0015] Step 4: Place the milky white gel in an oven to dry out the moisture to obtain a brown-yellow dry gel, which is then placed in a muffle furnace to remove impurities at high temperature and ground in a mortar to obtain nanoscale Ce. x Y x Zr ceramic powder material, wherein x is the doping molar ratio of each doping metal cation.

[0016] The zirconium oxide raw material is hydrated zirconium oxynitrate (ZrO(NO3)2·xH2O).

[0017] The zirconium oxide raw material Zr +4 The molar mass and total molar amount of metal cations of the dopant and the amount of ultrapure water used are in a ratio of 0.101 to 0.11 mol:1L.

[0018] The aqueous solution adopts ultrapure water.

[0019] The dopant is cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and yttrium nitrate hexahydrate (Y(NO3)3·6H2O) in a molar ratio of 1:1.

[0020] The polymerizing agent is acrylamide and N,N-methylenebisacrylamide, and the addition ratio is:

[0021] Zirconia raw material Zr +4 The ratio of the molar amount to the molar amount of acrylamide is 1:25;

[0022] The molar ratio of acrylamide to N,N-methylenebisacrylamide is 24:2.

[0023] The inducer is ammonium persulfate, and the addition ratio is: the molar ratio of acrylamide to ammonium persulfate is 24:1.

[0024] The temperature of placing the milky white gel in an oven to dry out moisture is 110° C. to 160° C., and the time is greater than or equal to 48 hours.

[0025] A nanometer-scale ZrO2 bioceramic powder material doped with Ce and Y elements in equal molar ratios prepared by the method, characterized in that ZrO2 is used as a matrix, two doping elements are introduced into ZrO2 by a sol-gel method, and nanometer-scale Ce is obtained. x Y x Zr ceramic powder material; the Ce x Y x The average powder grain size of the Zr ceramic powder material is less than 17nm, and the minimum grain size is about 14nm.

[0026] An application of the nano-scale ZrO2 bioceramic powder material doped with Ce and Y elements in equal molar ratios is characterized in that the nano-scale ZrO2 bioceramic powder material is prepared into a nano-scale bioceramic block material through a sintering process and applied to the field of dental restoration materials.

[0027] Beneficial Effects

[0028] The invention proposes a Ce and Y doped ZrO2 bioceramic material and a preparation method and application thereof, which relate to the field of multifunctional oxide powder materials and preparation thereof. The invention uses ZrO2 as a matrix and adopts a sol-gel method to introduce two doping elements into the ZrO2, and finally obtains a doped ZrO2 bioceramic powder material with an average powder grain size of less than 17nm, and the minimum grain size is about 14nm. The doped ZrO2 ceramic powder material can be further prepared into a nano-scale bioceramic block material through a sintering process, and has potential application value in the field of dental restoration materials.

[0029] In the present invention, the role of the polymerizing agents acrylamide and N,N-methylenebisacrylamide is to form a network structure with nano-scale voids by cross-linking, and the role of the inducing agent ammonium persulfate is to induce cross-linking polymerization of the polymerizing agents. Impurities introduced into the solution by these three compounds can be removed in the subsequent high-temperature treatment process.

[0030] Beneficial effects of the present invention:

[0031] 1. The present invention uses ZrO2 structure as the matrix and adopts sol-gel method to introduce two doping elements into the ZrO2 structure to obtain Ce-doped powder with an average particle size of less than 17nm. x Y x Zr ceramic powder material, the minimum grain size can reach 14nm. x Y x Zr ceramics provide strong protection.

[0032] 2. The present invention is used to synthesize Ce x Y xThe method used for preparing Zr ceramic powder material is the sol-gel method. The oxide synthesized by this method has the characteristics of fine powder particle size, uniform distribution and few impurities. In addition, this method has low synthesis temperature and low cost.

[0033] 3. The sol-gel method involves many raw materials, mainly zirconium nitrate provides Zr element, cerium nitrate and yttrium nitrate provide doping elements Ce and Y. In addition, there are some auxiliary agents that promote the formation of gel. Acrylamide and N,N-methylenebisacrylamide are used as polymerizers to provide nano-grids and the key to the formation of nano-ceramic powders. Ammonium persulfate is used as an inducer to reduce the reaction temperature.

[0034] The ratio parameters between the three auxiliary agents will directly affect the experimental period. +4 When the molar mass to acrylamide ratio is 1:25 and the molar ratio of acrylamide:N,N-methylenebisacrylamide:ammonium persulfate is 24:2:1, a gel can be formed at ~53°C for about 20 minutes after the raw materials are completely dissolved in ultrapure water.

[0035] Without changing the zirconium oxide raw material Zr +4 Based on the molar mass and molar ratio of acrylamide, when the molar ratio of acrylamide: N,N-methylenebisacrylamide: ammonium persulfate is 24:1:0.5, after the raw materials are completely dissolved in ultrapure water, the time required for gel formation at the same temperature is greatly increased to about 40 to 60 minutes. This increases the experimental cycle by about 2 to 3 times. Therefore, the ratio between the various components is crucial.

[0036] 4. Preparation of Ce by the present invention x Y x Zr ceramic powder is used to prepare nano-scale Ce x Y x Zr ceramics play an important role. Studies have shown that nano-scale ceramic powders have higher sintering activity, can achieve densification at lower temperatures, and are conducive to grain growth, which in turn makes the material have better mechanical properties; the introduction of a large number of nano-scale grains into ceramic materials can significantly improve the strength of ceramic materials and effectively prevent crack propagation; nanostructures can improve the fatigue life of ceramic materials and increase their service life in the human body, and are of great value as ZrO2-based dental restoration materials.

[0037] The present invention selects doping elements Ce and Y to prepare ZrO2 ceramic powder material. The presence of Ce and Y elements provides strong support for the stable existence of tetragonal ZrO2 ceramic material under room temperature. The Ce ion radius is larger than the Zr ion radius, which introduces lattice distortion in the ceramic material, and combined with the ZrO2 ceramic phase transformation toughening mechanism, it helps to improve the toughness of the ceramic material; the Y ion radius is about 25% larger than the Zr ion radius, and due to the different ion chemical valences, on the basis of generating lattice distortion, oxygen vacancies are also introduced, which increases the energy demand for phase transformation, thereby effectively hindering the ZrO2 phase transformation and promoting phase stability. In terms of resistance to hydrothermal aging, the doping of Ce elements makes ZrO2 ceramics have stronger resistance. At the same time, co-doping can improve the phase stability of ZrO2 ceramics, expand its scope of application, and reduce research costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The Ce prepared in Examples 1 to 6 of the present invention x Y x Actual photos of Zr powder oxide ceramic powder. From left to right, they are nanoscale Ce with molar doping concentrations of Ce and Y of 1mol%, 3mol%, 4mol%, 5mol%, 6mol% and 10mol%. x Y x Zr oxide ceramic powder material. With the increase of Ce element doping content, the powder changes from milky white to light yellow. x Y x The color of Zr oxide ceramic powder is the most intense light yellow.

[0039] Figure 2 The X-ray diffraction patterns of the products obtained from Examples 1 to 6 of the present invention are shown in Figure 1. From bottom to top, the Ce and Y element molar doping concentrations are 1 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol% and 10 mol% nanoscale Ce x Y x X-ray diffraction spectrum of Zr oxide ceramic powder material. It can be clearly seen from the figure that with the increase of doping content, Ce x Y x The diffraction intensity of the monoclinic phase diffraction characteristic peaks (-111) and (111) in the Zr oxide ceramic powder is significantly reduced, indicating that with the increase of doping concentration, the content of monoclinic phase with poor mechanical properties is significantly reduced. x Y x The monoclinic diffraction peak of the Zr oxide ceramic powder has completely disappeared, indicating that only the tetragonal phase ((101) diffraction characteristic peak) with excellent mechanical properties has been successfully obtained at room temperature, providing a strategic guarantee for the subsequent preparation of tetragonal zirconia with excellent performance.

[0040] Figure 3 The crystal face index of the products obtained in Examples 1 to 6 of the present invention corresponds to the grain size statistics. It can be clearly seen from the figure that Ce prepared by the sol-gel method x Y x The grain size of Zr oxide ceramic powder is between 12.28nm and 17.38nm, and the average grain size can be up to 15.22nm. x Y x The successful preparation of Zr ceramic powder provides material guarantee for the subsequent preparation of nano-doped zirconia ceramics with excellent performance.

[0041] Figure 4 The monoclinic phase content of the products obtained in Examples 1 to 6 of the present invention is clearly shown in the figure. As the doping concentration increases, Ce x Y x The monoclinic phase content of Zr ceramic powder gradually decreases until it disappears (6 mol%), indicating that the monoclinic phase content of zirconia with poor mechanical properties gradually decreases until it disappears with the increase of doping element concentration, providing powder guarantee for the subsequent preparation of zirconia with excellent performance. DETAILED DESCRIPTION

[0042] The present invention will now be further described with reference to the embodiments and the accompanying drawings:

[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0045] Unless otherwise specified, the experimental methods described in the following examples are all conventional methods; the reagents and materials described are all commercially available unless otherwise specified.

[0046] Example 1

[0047] A nanoscale Ce prepared by the present invention x Y x The preparation method of Zr oxide ceramic powder material, specifically using a sol-gel method to prepare Ce and Y doped zirconium oxide ceramic powder, comprises the following steps:

[0048] Step 1: Dissolve the zirconium oxide raw material ZrO(NO3)2·xH2O and dopants Ce(NO3)3·6H2O and Y(NO3)3·6H2O in ultrapure water, add them while stirring at room temperature, and finally obtain a transparent homogeneous solution. 3+ With Y 3+ The molar ratio of the zirconium oxide raw material to the total molar ratio of the metal element of the dopant is 1:1, and the molar ratio of the zirconium oxide raw material to the total molar ratio of the metal element of the dopant is 1:0.01. Then, the mixture is stirred at room temperature at a stirring speed of 200 rpm until it is completely dissolved in ultrapure water to obtain a transparent solution A.

[0049] Step 2, under room temperature, adding a polymerization agent (acrylamide and N,N-methylenebisacrylamide) and an inducing agent (ammonium persulfate) to solution A while stirring, and obtaining a light yellow transparent solution B after they are completely dissolved; wherein the zirconium oxide raw material Zr +4 The molar ratio of acrylamide to N,N-methylenebisacrylamide is 1:25; the molar ratio of acrylamide to N,N-methylenebisacrylamide is 24:2; the molar ratio of acrylamide to ammonium persulfate is 24:1. Impurities introduced by acrylamide, N,N-methylenebisacrylamide and ammonium persulfate can be removed in the subsequent high-temperature treatment process.

[0050] Step 3, heating solution B in a water bath until the temperature of solution B gradually rises to the gel point and a milky white gel appears, then stopping heating and stirring until the gel is complete, and then drying at 150°C for 48 hours to form a dry gel.

[0051] Step 4: Place the dry gel in a box furnace and sinter it at 800°C for 5 hours. After cooling to room temperature, place the fluffy material in the corundum crucible in an agate mortar and grind it thoroughly to obtain nano-scale Ce. x Y x Zr oxide ceramic powder material, the ceramic powder sample was recorded as 1 mol%.

[0052] Example 2

[0053] A nanoscale Ce prepared by the present invention x Y x The preparation method of Zr oxide ceramic powder material is basically the same as the method steps of Example 1, with the only difference that in step 1, the ratio of the molar amount of zirconium oxide raw material to the total molar amount of the metal element of the dopant is 1:0.03, and the sample is recorded as 3 mol%.

[0054] Example 3

[0055] A nanoscale Ce prepared by the present invention x Y xThe preparation method of Zr oxide ceramic powder material is basically the same as the method steps of Example 1, with the only difference that in step 1, the ratio of the molar amount of zirconium oxide raw material to the total molar amount of the metal element of the dopant is 1:0.04, and the sample is recorded as 4 mol%.

[0056] Example 4

[0057] A nanoscale Ce prepared by the present invention x Y x The preparation method of Zr oxide ceramic powder material is basically the same as the method steps of Example 1, with the only difference that in step 1, the ratio of the molar amount of zirconium oxide raw material to the total molar amount of the metal element of the dopant is 1:0.05, and the sample is recorded as 5 mol%.

[0058] Example 5

[0059] A nanoscale Ce prepared by the present invention x Y x The preparation method of Zr oxide ceramic powder material is basically the same as the method steps of Example 1, with the only difference that in step 1, the ratio of the molar amount of zirconium oxide raw material to the total molar amount of the metal element of the dopant is 1:0.06, and the sample is recorded as 6 mol%.

[0060] Example 6

[0061] A nanoscale Ce prepared by the present invention x Y x The preparation method of Zr oxide ceramic powder material is basically the same as the method steps of Example 1, with the only difference that in step 1, the ratio of the molar amount of zirconium oxide raw material to the total molar amount of the metal element of the dopant is 1:0.10, and the sample is recorded as 10 mol%.

[0062] Counterexample 1

[0063] A method for preparing Ce and Y doped zirconia ceramic powder by gelation, Hirano et al. used ZrOCl2·8H2O as Zr 4+Source, add H2O2 and NH4OH to ZrOCl2·8H2O aqueous solution, boil for 48h~72h to obtain monoclinic zirconium oxide particle gel. Mix CeCl3·7H2O solution and YCl3·6H2O solution, add ammonia water to the mixed solution while stirring to obtain precipitates Ce(OH)3 and Y(OH)3. Filter the precipitate, wash, dry, crush, calcine at 800℃~1150℃ in air, then ball mill with zirconium oxide balls in ethanol solution for 48h, and post-treat to obtain (Y,Ce)-TZP nanopowder. The Ce and Y co-doped zirconium oxide powder prepared by this method has a high monoclinic phase ratio, and the process is complicated and the cycle is long. (Hirano M, Inada H. Preparation, Sintering, Microstructure, and Thermal Stability of Y2O3-andCeO2-Doped Tetragonal Zirconia Ceramics[J]. Ceramics International, 1991, 17(6): 359~365.)

[0064] Counterexample 2

[0065] A method for preparing cerium-doped yttrium-stabilized zirconia powder based on yttrium-stabilized zirconia. Menvie et al. mixed commercial 8YSZ and 2-propanol to obtain a slurry, added ammonium cerium nitrate to the slurry, stirred for 2 minutes, and then air-dried at 100°C. After grinding, the slurry was calcined in a tube furnace at 450°C for 5 hours to obtain 10Ce-8YSZ powder with a particle size of 90nm. The grain size of the Ce and Y co-doped zirconia powder prepared by this method is much larger than that prepared by this method (the average grain size does not exceed 17nm). (Theunissen GSAM,Winnubst AJA,Burggraaf AJ.Effect of Dopants on the Sintering Behaviour and Stability of Tetragonal Zirconia Ceramics[J].Journal of European ceramic society,1992,9(4):251~263.)

[0066] 1. Photos of the real object

[0067] Ce prepared in Examples 1 to 6 of the present invention x Y x The actual photo of Zr powder oxide ceramic powder is shown as follows Figure 1From left to right, the Ce nanostructures are doped with Ce and Y at 1 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol% and 10 mol%. x Y x Zr oxide ceramic powder material.

[0068] 2. X-ray diffraction test

[0069] The products obtained from Examples 1 to 6 of the present invention were subjected to X-ray diffraction tests, and the results are as follows: Figure 2 From bottom to top, the Ce and Y element molar doping concentrations are 1 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol% and 10 mol% nanoscale Ce x Y x X-ray diffraction pattern of Zr oxide ceramic powder material.

[0070] The grain sizes of the products obtained in Examples 1 to 6 of the present invention can be calculated from the XRD test data. Using the Scherrer formula, the grain sizes of the nanoscale Ce with 6 doping concentrations were calculated. x Y x The grain size of Zr oxide ceramic powder material is shown in Figure 2. Figure 3 As shown, it can be calculated that the average grain size of the powder obtained by the present invention is less than 17 nm.

[0071] The monoclinic phase content of the products obtained in Examples 1 to 6 of the present invention can be calculated from the XRD test data. Using the relevant formula, the monoclinic phase content of the products obtained in Examples 1 to 6 of the present invention can be calculated from the XRD test data. x Y x The monoclinic phase content of Zr oxide ceramic powder material is shown in the following table. Figure 4 As shown in the figure, it can be seen that with the increase of doping concentration, nanoscale Ce x Y x The monoclinic phase content of Zr oxide ceramic powder material gradually decreases.

[0072] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0073] This method is mainly aimed at preparing uniform multi-element co-doped nano-ceramic powder, in which ceramic powders of different proportions are prepared, and the main focus is on the powder crystal structure and grain size. There are no performance parameters that can be compared.

Claims

1. Preparation of Nanoscale Ce by Sol-Gel Method x Y x The method of Zr ceramic powder material is characterized in that Here are the steps: Step 1: Dissolve the zirconium oxide raw material and dopant in an aqueous solution, add while stirring at room temperature until they are completely dissolved to obtain a transparent solution A; The zirconium oxide raw material Zr +4 The ratio of the molar mass to the total molar amount of metal cations of the dopant is 1:0.01-0.1; Step 2: Add the polymerizing agent and the inducing agent to solution A, stirring at room temperature until they are completely dissolved to obtain a light yellow transparent solution B; Step 3: Solution B is heated in a water bath to near the gel point, and a milky white gel begins to form until it is completely gelled; Step 4: Place the milky white gel in an oven to dry out the moisture to obtain a brown-yellow dry gel, which is then placed in a muffle furnace to remove impurities at high temperature and ground in a mortar to obtain nanoscale Ce. x Y x Zr ceramic powder material, wherein x is the doping molar ratio of each doping metal cation.

2. Preparation of nano-scale Ce by the sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The zirconium oxide raw material is hydrated zirconium oxynitrate (ZrO(NO3)2·xH2O).

3. Preparation of nano-scale Ce by the sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The zirconium oxide raw material Zr +4 The molar mass and total molar amount of metal cations of the dopant and the amount of ultrapure water used are in a ratio of 0.101 to 0.11 mol:1L.

4. Preparation of nano-scale Ce by sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The aqueous solution adopts ultrapure water or deionized water.

5. Preparation of nano-scale Ce by the sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The dopant is cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and yttrium nitrate hexahydrate (Y(NO3)3·6H2O) in a molar ratio of 1:

1.

6. Preparation of nano-scale Ce by sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The polymerizing agent is acrylamide and N,N-methylenebisacrylamide, and the addition ratio is: Zirconia raw material Zr +4 The ratio of the molar amount to the molar amount of acrylamide is 1:25; The molar ratio of acrylamide to N,N-methylenebisacrylamide is 24:

2.

7. Preparation of nano-scale Ce by the sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The inducer is ammonium persulfate, and the addition ratio is: the molar ratio of acrylamide to ammonium persulfate is 24:

1.

8. Preparation of nano-scale Ce by sol-gel method according to claim 1 x Y x The method of Zr ceramic powder material is characterized by: The temperature of placing the milky white gel in an oven to dry out moisture is 110° C. to 160° C., and the time is greater than or equal to 48 hours.

9. A nano-scale ZrO2 bioceramic powder material doped with Ce and Y elements in equal molar ratios prepared by the method according to any one of claims 1 to 8, characterized in that Using ZrO2 as the matrix, the sol-gel method was used to introduce two doping elements into ZrO2 to obtain nanoscale Ce x Y x Zr ceramic powder material; the Ce x Y x The average powder grain size of the Zr ceramic powder material is less than 17nm, and the minimum grain size is about 14nm.

10. An application of the nano-scale ZrO2 bioceramic powder material doped with Ce and Y elements in equal molar ratios as claimed in claim 9, characterized in that: The nano-scale ZrO2 bioceramic powder material is prepared into a nano-scale bioceramic block material through a sintering process and is applied in the field of dental restorative materials.

Citation Information

Patent Citations

  • Method for synthesizing spheroidic submicron tetragonal phase zirconia ceramic powder stabilized by yttrium and cerium

    CN103044034A

  • Zirconia ceramic powder and preparation method thereof

    CN110550952A

  • Preparation method of zirconium oxide microbeads

    CN111269011A

  • Zirconium oxide composite ceramic and preparation method thereof

    CN117623770A

  • Sol containing NANO zirconia particles for use in additive manufacturing processes for the production of 3-dimensional articles

    US20180127317A1